Exclusive breastfeeding frequency at 30 days of life: review of longitudinal studies - Mosquera, Paola Soledad; Lourenço, Bárbara Hatzlhoffer; Cardoso, Marly Augusto (Saúde e Sociedade, 2023)
Early life feeding can affect children’s development and survival. Adherence to breastfeeding practices and regular monitoring is essential. This study aims an integrative review of longitudinal studies on the frequency of exclusive breastfeeding (EBF) at 30 days of life. Articles were retrieved from the PubMed and LILACS databases. The combination of descriptors used was: “prospective study” and “breast feeding.” The search was limited to articles published between 2015 and 2020 in English, Spanish, and Portuguese. We selected 17 original studies. Despite their methodological differences regarding sample size and type, follow-up period, and EBF definition and measurement method, results indicated a high rate of breastfeeding initiation (≥86%) and a wide variation in the occurrence of EBF at 30 days (4.5% - 86%) with substantial decline (<60%) in 63% of the investigated areas. These results are far from complying with the recommendation from the World Health Organization of maintaining EBF up to the sixth month of children’s life and point to the need for further investigations with a standardized methodology for comparisons within and between countries, aiming at planning actions which support breastfeeding.